A Survey on Resilience in Information Sharing on Networks: Taxonomy and Applied Techniques - Batista, Agnaldo de Souza; Dos Santos, Aldri Luiz (ACM computing surveys, 2024)
Information sharing is vital in any communication network environment to enable network operating services take decisions based on the information collected by several deployed computing devices. The various networks that compose cyberspace, as Internet-of-Things (IoT) ecosystems, have significantly increased the need to constantly share information, which is often subject to disturbances. In this sense, the damage of anomalous operations boosted researches aimed at improving resilience to information sharing. Hence, in this survey, we present a systematization of knowledge about scientific efforts for achieving resilience to information sharing on networks. First, we introduce a taxonomy to organize the strategies applied to attain resilience to information sharing on networks, offering brief concepts about network anomalies and connectivity services. Then, we detail the taxonomy in the face of malicious threats, network disruptions, and performance issues, discussing the presented solutions. Next, we analyze the techniques existing in the literature to foster resilience to information exchanged on communication networks to verify their benefits and constraints. Throughout the text, we highlight and argue issues that restrain the use of these techniques during the design and runtime.